Levels of evidence and evidence of levels: Quo Vadis blood pressure? - Moodley, Rajen (SA Heart Journal, 2017)
There has historically been a series of guidelines for the diagnosis and management of elevated blood pressure. The recent publication by some members of the Joint National Committee (JNC 8), based only on randomised controlled trials, has generated much interest in view of newer levels for intervention and control. Clinicians and policymakers take their cue from these publications and hence there needs to be critical comment to promote rational prescribing. Comorbidities and “frailties” must dictate pharmaco-therapeutic choices to avoid risk in such patients. Conversely, we must guard against physician inertia also if guidelines seem to promote “relaxed” targets. This article seeks to cast some perspective on the current pronouncements.